Surgical techniques in ophthalmology oculoplasty and reconstructive surgery - Garg, Ashok; Kaynak-Hekimhan, Pelin; Alio, Jorge L.; Grover, Ak; Murube, Juan (New Delhi : Jaypee Brothers Medical Publishers, 2010)
Presenta aspectos básicos, técnicas quirúrgicas de alta tecnología, innovadoras y futuristas de los segmentos anterior y posterior de la oftalmología
Contents SECTION 1: External eye disases (Eyelids, lagrimal system and ocular surface disorders SECTION 2: Surgical management of eyelid disorders SECTION 3: Management of eyelid injuries SECTION 4: Eyelid retraction SECTION 5 : Congenital ptosis: Evaluation and management y otros más...
Texto en inglés
Incluye bibliografía
Keywords: OFTALMOLOGÍA; OJOS -- CIRUGIA; OCULOPLASTY